Substitutional boron doping of carbon materials - Ha, Sumin; Choi, Go Bong; Hong, Seungki; Kim, Doo Won; Kim, Yoong Ahm (KOREAN CARBON SOC, 2018)
A simple, but effective means of tailoring the physical and chemical properties of carbon materials should be secured. In this sense, chemical doping by incorporating boron or nitrogen into carbon materials has been examined as a powerful tool which provides distinctive advantages over exohedral doping. In this paper, we review recent results pertaining methods by which to introduce boron atoms into the sp(2) carbon lattice by means of high-temperature thermal diffusion, the properties induced by boron doping, and promising applications of this type of doping. We envisage that intrinsic boron doping will accelerate both scientific and industrial developments in the area of carbon science and technology in the future.